A HOMOSSEXUALIDADE DESCONSTRUÍDA EM LEVÍTICO 18,22 e 20,13 - Assis, Dallmer Palmeira Rodrigues de (2006)
This research presents a deconstruct reading of omosexualism presumable presented in Leviticus 18,22 and 20,13. The research found clear historical evidences of homosexual relations in many historical periods, even back to the X century. Also, the present study shows where and how this theme, books and authors related to homosexualism are found nowadays. These verses studied are part of a legal code called Holiness Code (Leviticus 17-26). The historical place for the composition of the code is initially found in the event of the returned Israel from exile in Babylon and goes until the beginning of Greek influence, centuries latter. Surely, Persia imperial period gains special relevance in the final composition of the Holiness Code . This period shows how relevant the idealization of the Code was to the community of faith in Judah and how important was to the community so it could not loose its existential identity. The exegetical analyses of the two verses attests how the author of Leviticus was not concerned and did not even mentioned homosexual relations in its fullness, but the texts did prohibit anal intercourse between males, in special occasions, gender mixture, violence to the male authority and every idea that would relate Israel to others communities and neighbors. The present research gets to the hermeneutic conclusion that Leviticus 18,22 e 20,13 knew nothing about modern homoerotic relations and were completely silent to the concept of homosexualism in the post exilic Judah. So this research wants to be the motivation to the discussion on the issue of homosexualism in the Academy and in the religious communities. As studied in this paper, there is nothing that the hebrew bible can say to oppress men and women that want to live their life in the free expression of a unisexual relation today